Cardiovascular adaptations in judo: a narrative review - Rossi, C.; Giustino, V.; Patti, A.; Roklicer, R.; Manojlovic, M.; Trivic, T.; Fukuda, D.; Bianco, A.; Drid, P. (Frontiers in Sports and Active Living, 2025)
Judo is a high-intensity combat sport requiring substantial aerobic and anaerobic capacity. Although research has explored the physiological demands of different sports over the years, few studies have investigated the specific cardiovascular adaptations that occur in judoka. This narrative review examines these adaptations by focusing on cardiac function, heart rate variability (HRV), and hemodynamic responses, with the aim of summarizing the effects of judoka training on cardiovascular health and the relationship with athletic performance. Judo training improves aerobic capacity, with VO2max values similar to those of team sports athletes. It stimulates physiological hypertrophy of the left ventricle, improving cardiac function. Autonomic regulation shows a parasympathetic predominance, indicating better stress adaptation. Vascular adaptations include increased arterial elasticity and optimal blood pressure management, with judoka exhibiting lower blood pressure values than the general population. In summary, these adaptations promote cardiovascular health and improve athletic performance, although monitoring is essential to prevent overtraining and long-term issues.